Cephalic Vein Thrombosis Plus Prosthesis Placement For Hemodialysis (Journal of Pharmaceutical Negative Results, 2023)
Objective: contribution of new bibliographic material, useful in updating knowledge since it refers to expert criteria regarding the diagnosis and treatment of thrombosis of arteriovenous fistula, treated with prosthesis. Brief description of the case: well-functioning vascular access is essential for hemodialysis patients. Thrombosis is the main cause of vascular access failure. Thrombectomy and repair allow it to keep it functional and prolong its patency. Therefore, this approach remains the main objective for access rescue and prolongation of the vascular patency rate. Conclusions: PTFE (Poly-tetra-harin-ethylene) is the material from which the most commonly used vascular prosthesis is composed within our country VascuGraft, as it provides a unique flexibility, torsion-resistant that is porous enough to encourage cell growth, provides maximum protection against kinking or twisting of the prosthesis implantation, yet offers maximum protection against blood loss, suture pullout, tearing or delamination. The silicone prosthesis (polydimethylsiloxane, PDMS) provides stability and longitudinal and circumferential elasticity, greater suture retention strength and resistance to punctures, permeability and adaptability exceed the Graft type of prosthesis; however, by the cost, it is difficult to access.